Proceedings of the NSF/UCR U.S.-Costa Rica Workshop on the Costa Rica earthquakes of 1990-1991 : Effects on soils and structures - Leon, Roberto T. (1993)
On April 22, 1991 a major earthquake (Ms= 7.5) shook the eastern part of Costa Rica and northeastern Panama. The earthquake caused 53 deaths, left 30,000 people homeless, and caused over half a billion dollars in property damage and lost revenue. This was the sixth major shock of a series that began with two major events (M = 6.4 and 7.0) centered south of the Nicoya Peninsula on March 25: 1990, and which were followed by three moderate earthquakes (Ms = 6. 4, 6. 3, and 6 .1) during 1991. This report summarizes the results of a workshop on the effects of both the April 22, 1991 Limon earthquake and other earthquakes that occurred in Costa Rica in 1990-1991. The April 1991 earthquake presents a unique opportunity tp study the performance of structures sited on very soft and liquefiable soils. The workshop intended to study and identify research topics dealing with analysis, retrofit, and design techniques to mitigate damage when poor soil conditions exist. Areas identified as possible research topics included:* Characterization of ground motion * Seismic hazard and seismic risk analysis * Response spectra and input motions * Liquefaction and large ground displacements * Highway damage due to liquefaction * Performance of port facilities * Dynamic response of earth dams * Earthquake effects on existing landslides * Large ground deformations under bridge supports * Movements of bridge superstructures * Performance of precast building systems * Evaluation and rehabilitation of buildings * Performance of under-reinforced masonry * Permanent ground displacement effects on buried pipelines * Seismic vulnerability of the Central Valley of Costa Rica For each of these general topics, detailed research projects were discussed and summaries prepared. These summaries appear in Part 2 of this report. To complement the information already available in the literature, written contributions from the keynote speakers at the workshop are included as Part 3 of this report. The workshop participants identified areas where more research was needed and developed topics for joint U.S.-Costa Rica research, with emphasis on lifelines (bridges, water and electrical systems, emergency services, and key industrial facilities). The results of these research projects will be directly applicable to the U.S. practice since large areas of the U.S., including the San Francisco Bay Area, the Mississippi River Valley, Charleston, s.c., Boston, MA, and other are prone to encounter similar problems if subjected to strong ground shaking.